2020
DOI: 10.1186/s12576-020-00782-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exogenous and endogenous estrogen on thermoregulatory responses to mild heat and the interaction with light and dark phases

Abstract: The present study aimed to determine the influence of estradiol (E2) and the interaction with circadian phases on thermoregulatory responses to mild heat in female rats. Heat loss and production during 3-h exposure to the environment at an ambient temperature of 28–34 °C were assessed by measuring abdominal temperature (Tabd), tail skin temperature, and oxygen consumption in ovariectomized rats with and without E2 replacement (OVX + E2 and OVX, respectively) and in control rats in the proestrus (P) and diestru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It is well known that the long‐term administration of androgens often has adverse effects and that gonadal hormones, for example, estrogen and progesterone, affect thermogenesis in females, including experimental animals. 16 , 17 , 23 In addition, it has been reported that estrogen increases locomotor activity in female rodents. Female rats show the greatest locomotor activity in the proestrus stage, when they also display concomitant increases in serum estrogen levels, and estrogen supplementation increases locomotor activity in ovariectomized female rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the long‐term administration of androgens often has adverse effects and that gonadal hormones, for example, estrogen and progesterone, affect thermogenesis in females, including experimental animals. 16 , 17 , 23 In addition, it has been reported that estrogen increases locomotor activity in female rodents. Female rats show the greatest locomotor activity in the proestrus stage, when they also display concomitant increases in serum estrogen levels, and estrogen supplementation increases locomotor activity in ovariectomized female rats.…”
Section: Discussionmentioning
confidence: 99%
“…Other problems with PCOS animal models include the fact that the safety of chronic hormone manipulation has not been fully evaluated and that changes in locomotor activity and thermogenesis have never been examined in such models. It is well known that the long‐term administration of androgens often has adverse effects and that gonadal hormones, for example, estrogen and progesterone, affect thermogenesis in females, including experimental animals 16,17,23 . In addition, it has been reported that estrogen increases locomotor activity in female rodents.…”
Section: Discussionmentioning
confidence: 99%